(untitled) - Johnson, Brian T. (Bolton, Mass., 2006)
In "The Spirit of Service," the contributing authors explore the intersection of faith, service, and social justice in higher education. Reflecting upon the role that higher education plays in preparing future generations of citizens and leaders, this book asserts that spirituality and values necessarily involve one's person--and that educators must begin to connect student learning with the human experiences of faith, service, and commitment to social justice.
Keywords: Service learning,Social justice,Universities and colleges; Study and teaching; United States,United States,United States